3x+8=89-6

Simple and best practice solution for 3x+8=89-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+8=89-6 equation:


Simplifying
3x + 8 = 89 + -6

Reorder the terms:
8 + 3x = 89 + -6

Combine like terms: 89 + -6 = 83
8 + 3x = 83

Solving
8 + 3x = 83

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 3x = 83 + -8

Combine like terms: 8 + -8 = 0
0 + 3x = 83 + -8
3x = 83 + -8

Combine like terms: 83 + -8 = 75
3x = 75

Divide each side by '3'.
x = 25

Simplifying
x = 25

See similar equations:

| 2/3w=8 | | 3(x+7)2+17=25 | | 1/2x=3 | | p=25 | | -3/4(12x-8)=-18 | | 20-4x=5x-35 | | a^2+2a+8=0 | | x-6=42 | | 4x+y=-20 | | 2p-1=3y+11 | | 29-H=207 | | 9x-4x+32=6x-21 | | 33=0+3y | | 3y-2y=8x | | y=3/5+9 | | y=2.5x-2 | | 21/p+1=8 | | a^2-2a+8=0 | | 15+(-4x-18)=9 | | 5n-7=3n-9 | | a/-6+8=12 | | 1-k=27 | | c/4=8 | | d/-2+5=7 | | 16-(9b+3)=4 | | 2(x-2)=16-3x | | -7x+y=-4 | | (2s+4)(2s-4)= | | 7x^2-5=2 | | x/4+10=34 | | 6x-2=-4x+7 | | -9=-20+a |

Equations solver categories